Identificação de áreas degradadas por extração de argila no município de Ourinhos (SP): recuperação do passivo ambiental e proteção dos recursos hídricos - Ribeiro, João Pedro Marques [UNESP] (2012)
More and more industrial activities are concerned about environment damages, and mining is an example. In Brazil there is a specific legislation for mining, which requires degraded areasrecovery. However, the environmental liability generated often is not properly compensated. Historically, Ourinhos has in the ceramicist and pottery sectors important components of the local economy. The clay pits distributed along the Paranapanema River were found abandoned in large numbers. The proximity to the banks of the river exacerbates the problem, causing sedimentation in water bodies, thalweg extension, decreasing water flow and damage to hydroelectric system installed throughout the river course. This work performed the diagnosis and mapping of mineral exploration area in Ourinhos (SP), along the Paranapanema River using satellite images, GIS and field campains. It was checked which pits were on permanent preservation areas (PPA) and its current state. Of a total of 27 pits mapped, 13 are total or partly within the areas of PPA. It was developed a recovery plan that was economically viable and environmentally responsible, based on riprian vegetation recomposition and criation of a thematic park.